Faktor-faktor yang mempengaruhi pertumbuhan laba pada Bank Umum Konvensional yang terdaftar di BEI periode tahun 2018-2020 - Febriyanti, Sita; Aini, Nur (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Profit growth is a ratio used to see a business enterprise’s capability to increase income in comparison to the previous period. This study targets to examine the elements that affect profit growth in conventional business banks indexed on the IDX for the length 2018-2020. The populace on this examine are conventional business banks indexed at the IDX for the duration 2018-2020, obtained a population of 45 conventional business banks indexed at the IDX. This examine uses secondary facts inside the form of numbers that are processed right into a statistical measurement scale, so it’s called secondary facts. The analytical method used on this studies is statistics analysis the use of multiple linear regression test. The consequences of this look at suggest that CAR has a positive impact on bank income growth, BOPO has a negative impact on bank income growth, at the same time as NPL and LDR have no impact on income growth of conventional business banks indexed on the IDX for the 2018-2020 period.